Heat stress in crop plants: its nature, impacts and integrated breeding strategies to improve heat tolerance. Issue 6 (27th October 2014) - Jha, Uday Chand; Bohra, Abhishek; Singh, Narendra Pratap; Tuberosa, R.
Abstract Increasing severity of high temperature worldwide presents an alarming threat to the humankind. As evident by massive yield losses in various food crops, the escalating adverse impacts of heat stress (HS) are putting the global food as well as nutritional security at great risk. Intrinsically, plants respond to high temperature stress by triggering a cascade of events and adapt by switching on numerous stress‐responsive genes. However, the complex and poorly understood mechanism of heat tolerance (HT), limited access to the precise phenotyping techniques, and above all, the substantial G × E effects offer major bottlenecks to the progress of breeding for improving HT. Therefore, focus should be given to assess the crop diversity, and targeting the adaptive/morpho‐physiological traits while making selections. Equally important is the rapid and precise introgression of the HT‐related gene(s)/QTLs to the heat‐susceptible cultivars to recover the genotypes with enhanced HT. Therefore, the progressive tailoring of the heat‐tolerant genotypes demands a rational integration of molecular breeding, functional genomics and transgenic technologies reinforced with the next‐generation phenomics facilities.